Blue Ocean Strategy (BOS) Public Relations of Kampung Wisata Baluwarti Surakarta in Developing Village Branding - Prita Suci Nurcandrani; Ade Tuti Turistiati; Sefy Andhriany; Dinda Intan Nurulina (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
This study aims to analyze how the Baluwarti Surakarta Tourism Village builds village branding. The components of the formation of village branding include the physical potential of the village that is unique, natural, rare, and has the concept of community empowerment. In formulating village branding, this study uses the Blue Ocean Strategy in which competition with other tourist villages is irrelevant. The use of digital branding is also associated with the village branding business in Baluwarti Tourism Village. The research method used is descriptive qualitative and data collection techniques with direct observation to the research locus and in-depth interviews with research informants. The results of this study indicate that Surakarta's Baluwarti Tourism Village needs to have a Public Relations whose role is to optimize the role of all stakeholders in achieving village branding, especially empowering the Baluwarti community and utilizing effective and efficient communication media.